2023
DOI: 10.3390/polym15061342
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell Membrane as a Biomaterial for Bone Regeneration

Abstract: The physicochemical features of the avian eggshell membrane play an essential role in the process of calcium carbonate deposition during shell mineralization, giving rise to a porous mineralized tissue with remarkable mechanical properties and biological functions. The membrane could be useful by itself or as a bi-dimensional scaffold to build future bone-regenerative materials. This review focuses on the biological, physical, and mechanical properties of the eggshell membrane that could be useful for that pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 143 publications
0
11
0
Order By: Relevance
“…Likewise, the ability of the ESM to prevent the internalisation of bacteria and thus its antibacterial properties are widely accepted (Ahlborn and Sheldon 2006). The presence of desmosine and isodesmosine crosslinks allows the ESM to be insoluble, allowing it to support the embryo during development (Torres-Mansilla et al 2023).…”
Section: Physical Properties and Componentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Likewise, the ability of the ESM to prevent the internalisation of bacteria and thus its antibacterial properties are widely accepted (Ahlborn and Sheldon 2006). The presence of desmosine and isodesmosine crosslinks allows the ESM to be insoluble, allowing it to support the embryo during development (Torres-Mansilla et al 2023).…”
Section: Physical Properties and Componentsmentioning
confidence: 99%
“…It has been widely observed that the ESM is a proteinrich structure containing over 500 different proteins and acts as a natural source of collagen, fibronectin, proteoglycans, glycoproteins, hyaluronic acid and many amino acids such as arginine, glutamic acid, histidine, cystine, and proline which are found in high concentrations (Chi and Zhao 2009, Guru and Dash 2014, Ahmed et al 2019a, Mensah et al 2021. In addition to the proteins and amino acids, CaCO 3 is also present in the ESM, this is due to the presence of a level of mineralisation in the outer membrane (Arias et al 1993, Shi et al 2021, Torres-Mansilla et al 2023. The close resemblance in structure between the ESM and extracellular matrix (ECM) and vast biological The ESM provides a natural source of substances vital for tissue engineering and wound healing.…”
Section: Biological Propertiesmentioning
confidence: 99%
See 3 more Smart Citations